Psychosocial risks for constipation and soiling in primary school children - Joinson, Carol (Eur Child Adolesc Psychiatry, 2018)
To examine prospective associations between psychosocial problems and childhood constipation and soiling. We used latent classes of constipation and soiling (‘constipation alone’, ‘soiling alone’, ‘constipation with soiling’) extracted from longitudinal maternally reported data on constipation (4–10 years) and soiling (4–9 years) from 8435 children (4353 males, 4082 females) from the ALSPAC cohort. We examined the association between maternally reported psychosocial problems at 2–3 years (difficult temperament, behaviour/emotional problems, temper tantrums, behavioural sleep problems and stressful events) and the latent classes using multinomial logistic regression adjusted for a range of confounders relating to the child and family (reference category = normative latent class with very low probability of constipation/soiling). Difficult temperament and emotional/behaviour problems were associated with increased odds of constipation and soiling. Associations were generally strongest for ‘constipation with soiling’, e.g. difficult mood: 1.42 (1.23–1.64); behaviour problems: 1.48 (1.28–1.71); temper tantrums: 1.89 (1.34–2.65); lack of a regular sleep routine 2.09 (1.35–3.25). Stressful life events were associated with constipation alone [1.23 (1.12–1.36)] and constipation with soiling [1.32 (1.14–1.52)], but not soiling alone. Additional comparisons of the non-normative latent classes provided evidence for differential associations with the risk factors, e.g. frequent temper tantrums were associated with a greater than twofold increase in the odds of constipation with soiling versus constipation alone. Psychosocial problems in early childhood are risk factors for constipation and soiling at school age. An increased understanding of early risk factors for constipation and soiling could aid the identification of children who require treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00787-018-1162-8) contains supplementary material, which is available to authorized users.